(Why) does comment presentation order matter for the effects of user comments? Assessing the role of the availability heuristic and the bandwagon heuristic. Issue 4 (8th August 2021) - Kümpel, Anna Sophie; Unkel, Julian
ABSTRACT: Research has shown that user comments influence peoples' perceptions, with recent evidence suggesting that comment presentation order (e.g., whether comments are presented prior to/after the commented item) may alter the strength of comments' effects. Considering the implications of this finding for content producers, the informed design of experiments, and the interpretation of prior studies, this study aimed (1) to replicate a recent study on comment presentation order, and (2) to identify why (negative) comments presented after an article seem to have stronger effects on users' perceptions. A pre-registered experiment with 325 participants provided inconclusive evidence of the predicted presentation order effect and did not allow for further investigations of the underlying reasons. Overall, the findings highlight the ongoing need for studying the conditions under which effects of user comments occur.